ПОМОГИИИИИИИИИИИИИИИИИИИИИИИИИИТЕЕЕЕЕЕЕЕЕЕЕЕЕЕЕ!!!!!!!!!!!

СЕГОООООООООДНЯЯЯ!!!!!СРОООООООООООЧНОООО!!!!!

1)Упростите выражения:

(3x^2+y)(2y-5x^2)

(7x-1)(x^2-4x+2)

(a^2+b^2)(2a-b)-ab(b-a)

-8b(b+3)(2-b^2)

2)Разложите на множетели:

2x^5+5x^4-2x^2-5x

3a-3b+(a-b)^2

3)Докажите тождество:

x^5+1=(x+1)(x^4-x^3+x^2-x+1)

4)Представьте в виде произведения:

x^2-2xy+x-xz+2yz-z

a^3-ab-a^2b+a^2

1

Ответы и объяснения

  • mayli
  • светило науки
2012-04-04T00:02:12+04:00

1)(3x^2+y)(2y-5x^2)=6x^2y-15x^4+2y^2-5x^2y=-15x^4+x^2y+2y^2

 

(7x-1)(x^2-4x+2)=7x^3-28x^2+14x-x^2-4x-2=7x^3-29x^2+18x-2

 

(a^2+b^2)(2a-b)-ab(b-a)=2a^3-a^2b+2ab^2-b^3-ab^2+a^2=2a^3-b^3-a^2b+ab^2+a^2

 

-8b(b+3)(2-b^2)=-8b(2b-b^3+6-3b^2)=-16b^2+8b^4-48b+24b^3=8b^4+24b^3-16b^2-48b

 

2)2x^5+5x^4-2x^2-5x=2x^5-2x^2+5x^4-5x=2x^2(x^3-1)+5x(x^3-1)=(2x^2-1)(x^3-1)

 

3a-3b+(a-b)^2=3(a-b)+(a-b)^2=(3+a-b)(a-b)

 

3)x^5+1=(x+1)(x^4-x^3+x^2-x+1)

 (x+1)(x^4-x^3+x^2-x+1)=x^5-x^4+x^3-x^2+x+x^4-x^3+x^2-x+1=x^5+1